2014
DOI: 10.3892/mmr.2014.2527
|View full text |Cite
|
Sign up to set email alerts
|

Duhuo Jisheng Decoction-containing serum promotes proliferation of interleukin-1β-induced chondrocytes through the p16-cyclin D1/CDK4-Rb pathway

Abstract: Duhuo Jisheng Decoction (DHJSD) is a traditional Chinese herbal medicine that has multiple uses, including as a treatment for osteoarthritis (OA). However, the molecular mechanisms underlying the therapeutic effects of DHJSD on OA remain unknown. In the present study, a serum pharmacological method was applied to investigate the effects of DHJSD on the proliferation of chondrocytes treated with interleukin‑1β (IL‑1β) in vitro. This is a cell model commonly used to reproduce the mechanisms involved in degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…We firstly reported that Cyclin D1 was relatively different expressed in different OA grade patients. Wu et al [19] identified that when over-expression of Cyclin D1, the proliferation of chondrocyte was increased. Beier et al [20] further verified the Cyclin D1 in vivo for the promotion of the proliferation of chondrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…We firstly reported that Cyclin D1 was relatively different expressed in different OA grade patients. Wu et al [19] identified that when over-expression of Cyclin D1, the proliferation of chondrocyte was increased. Beier et al [20] further verified the Cyclin D1 in vivo for the promotion of the proliferation of chondrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7, DHJSD has an overall effect to eliminate "fenghan-shi", respectively, and thus to relieve pain of "Bi Zheng" through promoting "Gan" and "Shen" function and therefore strengthen the bones and tendons [30] . It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…It also improves circulation and remove stasis of "Qi" and "Xue", reduces tissue swelling and relieves pain [20,22,23,26,32,39,40] . Some pharmacological studies have demonstrated that DHJSD may have effects of analgesia, immune function regulation, blood vessel dilation, anti-inflammation, and antiplatelet aggregation [20,22,23,26,32,39,40] . In a study of the aging-related osteoarthritis, another common bone degenerative disease, Chen et al found that DHJSD may inhibit VEGF and HIF-1α to retard cartilage degradation in a rabbit model of osteoarthritis [53] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations